Development of Physical Education, Sport and Health Leaning Model in Inclusive Primary School - et. al., Sumaryanti, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
People with disability worldwide are not considering in many tasks especially in physical education and sports, they are somehow ignored. The aims of this research were to disseminate a Physical Education (PE), Sport and Health learning model instruction to a broader field. The research sampling were physical education teachers, sport teachers, and students from Yogyakarta State University were recruited. The research instruments were a test, questionnaire, and observation guide. The data were analyzed using descriptive techniques. The results were disseminated effectively by explaining the concept and model visualization, training teachers by giving them the freedom to apply the concept adjusted to condition, peer teaching through simulation in small groups, and transferring from teachers to students according to the model. The model was very easy to apply. The including of students with disabilities in school-based on physical education (PE), sports and health was common practice. However, the engagement and interaction of all students in this environment were observed. The new learning model has improved the physical education teaching skills. In conclusion there was a good interaction between normal student and disables students were therefore observed.